Unique Aspects of Usage of the Quadratic Cryptanalysis Method to the GOST 28147-89 Encryption Algorithm - Akhmedov, Bardosh; Aloev, Rakhmatillo (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
In this article, issues related to the application of the quadratic cryptanalysis method to the five rounds of GOST 28147-89 encryption algorithm are given. For example, the role of the bit gains in the application of the quadratic cryptanalysis method, which is formed in the operation of addition according to mod232 used in this algorithm is described. In this case, it is shown that the selection of the relevant bits of the incoming plaintext and cipher text to be equal to zero plays an important role in order to obtain an effective result in cryptanalysis